Hardness Measurement of Al-Mg-Si Alloy: Experimentation and Theoretical Validation - Kumar N. (My University, 2025)
In the present work, first time hardness enhanced due to the precipitation of β″- and β′-phases in the solution treated (S.T)-6082 Al alloy was calculated with the help of empirical relations, and experimentally validated via Vickers’s hardness tester. For this, S.T-6082 Al alloy underwent for the differential scanning calorimetry study at the different heating rate from 5°C/min to 20°C/min. The isochronal heat treatment was performed up to 244°C and 297°C, respectively, at the heating rate of 15°C/min followed by the rapid water quenching for evolving the β″- and β′-phases. The Kissinger plot was drawn to calculate the activation energies required (104 kJ/mol and 110 kJ/mol) for the precipitation of β″- and β′-phases, respectively. Arrhenius relationship (lnΔHV=-ERT+lnΔHV0) and Kissinger equation ((ln(BT2)=-ERT+Constant) were used to calculate the rise in hardness due to the precipitation of β″- (30.7 HV) and β′-phases (18.64 HV), respectively. © 2022, ASM International.